2022
DOI: 10.7759/cureus.32727
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antibiotic Lavage in Total Knee Replacement to Prevent Postoperative Infection

Abstract: To determine the effectiveness of using antibiotic lavage in preventing postoperative infections in total knee replacement (TKR) patients. MethodsData on all patients who underwent TKR, either primary or secondary, during the period from May 2015 to April 2019 were collected. Many factors (both patient-related and surgery-related) that can increase the risk of surgical site infection (SSI) were taken into consideration to eliminate confounding factors. ResultsA total of 685 patients were identified; out of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Some experimental studies on in vivo models have reported that antibiotics decrease the quantity of the microorganisms from the wound surface when compared with other irrigants 14,15 . Almaawi et al 16 demonstrated that the use of intraoperative vancomycin lavage during total knee arthroplasty (TKA) was associated with a decrease in the incidence of postoperative surgical site infection when compared with no antibiotic lavage; however, this did not reach statistical significance. Conversely, other investigators have demonstrated that additives including antibiotics have a negative effect on wound healing and increase reinfection rates when compared with other solutions such as normal saline 9,14,15,17 .…”
Section: Traditional Irrigantsmentioning
confidence: 99%
“…Some experimental studies on in vivo models have reported that antibiotics decrease the quantity of the microorganisms from the wound surface when compared with other irrigants 14,15 . Almaawi et al 16 demonstrated that the use of intraoperative vancomycin lavage during total knee arthroplasty (TKA) was associated with a decrease in the incidence of postoperative surgical site infection when compared with no antibiotic lavage; however, this did not reach statistical significance. Conversely, other investigators have demonstrated that additives including antibiotics have a negative effect on wound healing and increase reinfection rates when compared with other solutions such as normal saline 9,14,15,17 .…”
Section: Traditional Irrigantsmentioning
confidence: 99%
“…In total hip and total knee arthroplasty, a vast body of literature has outlined prosthetic joint infection (PJI) predictors, diagnostic criteria, and mitigation strategies. 1,3,6,20,23,24,27,28,34,35,39 In contrast, relatively little has been published regarding infection in TAA. 2…”
Section: Introductionmentioning
confidence: 99%